Sales Scale, Non-Pastoral Employment and Herders’ Technology Adoption: Evidence from Pastoral China - Zhipeng Huang; Yan Zhang; Yi Huang; Gang Xu; Shengping Shang (Land, 2022)
The adoption of livestock husbandry technologies has been an important factor affecting the welfare of herders and the efficiency of grazing-based livestock production and grassland protection in China’s pastoral areas. The small-scale herder is the main body of grassland-based grazing husbandry, and so technology adoption is particularly important, though it is currently scarce. To identify the factors influencing technology adoption behavior by Chinese herders, especially its effect on the scale of livestock sales and non-pastoral employment (NPE), we conducted a survey in the Gansu and Qinghai provinces of China with a sample of 296 herder households. The results show that the scale of livestock sale promotes the adoption of technology, while non-pastoral employment has a generally negative effect. In detail, the substitution effect of NPE is positive, but the wealth effect is negative. In addition, NPE and its wealth effect have moderating effects that can enhance the effect of the sales scale on the adoption of herders’ technology. After distinguishing the technologies into profit-seeking technology and pro-environmental technology, we found that NPE and its substitution effect have a significant influence on pro-environmental technology, while the wealth effect has a significant impact on both profit-seeking and pro-environmental technology. Environmental awareness and altruism also have significant positive impacts on pro-environmental technology. These findings are relevant to policy implications dealing with technology adoption in pastoral areas.